THE CONCEPTUAL MODEL TO EDUCATE CHILDREN WITH AUTISM IN SOCIAL INTERACTION SKILLS USING VIDEO MODELLING - AHMAD AZAHARI, IMAN NUR NABILA (2020)
This research has discovered several challenges face by children with Autism Spectrum Disorder (ASD). The key problem identified; children with ASD face obstacles and difficulties in managing their impairments, particularly in communication and social interaction. Impairment in social ability may cause "eventual social anxiety, depression, isolation and other undesirable outcomes”. In addition, these impairments may also affect children with ASD struggles with communication skills and therefore being unable to learn basic social interaction skills.